2000
DOI: 10.1128/jb.182.12.3593-3596.2000
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide Production Is Required for Development of Escherichia coli K-12 Biofilm Architecture

Abstract: Although exopolysaccharides (EPSs) are a large component of bacterial biofilms, their contribution to biofilm structure and function has been examined for only a few organisms. In each of these cases EPS has been shown to be required for cellular attachment to abiotic surfaces. Here, we undertook a genetic approach to examine the potential role of colanic acid, an EPS of Escherichia coli K-12, in biofilm formation. Strains either proficient or deficient in colanic acid production were grown and allowed to adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
441
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 579 publications
(463 citation statements)
references
References 22 publications
(22 reference statements)
9
441
1
5
Order By: Relevance
“…We interpret the inclusion of the cys mutants in this class as the result of a requirement for activated sulphur in the biosynthesis of V. parahaemolyticus CPSA. Although the relative importance of CPSA in biofilm formation is consistent with observations in many organisms Danese et al, 2000;Sutherland, 2001), the fact that CPSA played a central role in both cell types was somewhat surprising in light of prior data demonstrating dramatic differences in the amount of CPSA produced by OP and TR strains (Enos-Berlage and McCarter, 2000). Perhaps TR strains produce sufficient CPSA to foster biofilm development and the additional CPSA produced by OP strains alters the properties and the architecture of the biofilm.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We interpret the inclusion of the cys mutants in this class as the result of a requirement for activated sulphur in the biosynthesis of V. parahaemolyticus CPSA. Although the relative importance of CPSA in biofilm formation is consistent with observations in many organisms Danese et al, 2000;Sutherland, 2001), the fact that CPSA played a central role in both cell types was somewhat surprising in light of prior data demonstrating dramatic differences in the amount of CPSA produced by OP and TR strains (Enos-Berlage and McCarter, 2000). Perhaps TR strains produce sufficient CPSA to foster biofilm development and the additional CPSA produced by OP strains alters the properties and the architecture of the biofilm.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, consistent with work in many organisms (e.g. Danese et al, 2000), CPS in V. parahaemolyticus appears to play an important role in adherence (measured by crystal violet), and establishment of three-dimensional biofilms (i.e. pellicle formation and microcolony/pillar formation in the submerged coverslip assay).…”
Section: Cpsa Production Is Critical For Op and Tr Biofilm Formationmentioning
confidence: 62%
“…The activation of the Rcs phosphorelay results in an increase in the expression of the extracellular polysacchar-ide colanic acid (Gottesman et al, 1985). As the expression of colanic acid is required for the maturation of biofilms formed by E. coli, this suggests a positive role for the Rcs phosphorelay in the regulation of biofilm maturation (Danese et al, 2000b). On the other hand, activation of the Rcs phosphorelay has been shown to repress the expression of genes encoding surface adhesins, such as antigen 43 (Ag43) and curli, and it has been reported that overproduction of RcsB (a situation that mimics the activation of the Rcs phosphorelay) inhibits the expression of the flhDC operon, encoding the master regulators of flagella biosynthesis (Ferrières & Clarke, 2003;Francez-Charlot et al, 2003;Vianney et al, 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Over the past few years, a role for the Rcs phosphorelay in biofilm formation by Escherichia coli has been proposed (Danese et al, 2000b;Ferrières & Clarke, 2003). The Rcs phosphorelay is composed of the sensor kinase, RcsC, the histidine-phosphotransfer (HPt)-containing protein RcsD and the cytoplasmic RcsB response regulator (Huang et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%
“…Positive cultures are surrounded by a dark blue halo. Overnight cultures were spotted and plates were incubated at 28 uC for 48 h (Danese et al, 2000).…”
Section: Methodsmentioning
confidence: 99%